Viewpoint: Transport's digital age transition - Glenn Lyons (Journal of Transport and Land Use)
2014 marks the 25th birthday of the World Wide Web. We have seen some remarkable developments as part of the digital age revolution in the last quarter of a century. These have taken place concurrently with a motor age that is possibly past its prime. A number of major motor manufacturers have faced disappointing sales or financial crisis alongside several countries seeing a halt to the historic trend of growing car use. The co-existence of the motor age and the digital age prompts this paper to consider the hypothesis that society is undergoing a fundamental transition from a regime of automobility to something significantly different. The paper considers what has characterized the motor age and proceeds to examine the digital revolution and how this is changing people’s means to access people, goods, services and opportunities. The range of interactions between the motor age and the digital age are addressed, underlining the difficulty in establishing the net consequence of one for the other. The new debates concerning ‘peak car’ are considered in which the digital age is identified as potentially one key factor responsible for observed changes in car use. The paper then focuses upon a socio-technical conceptualization of society known as the Multi-Layer Perspective to examine its hypothesis. Support or not for the hypothesis is not, as yet, established. Transport’s future in the digital age is uncertain and the paper sets out some views on resulting policy considerations and research needs.